Primary gastrointestinal aspergillosis 6 months after allogeneic hematopoietic cell transplantation: a case report. Issue 3 (14th April 2013) - Mora, D.; Barba, P.; Ruiz, I.; Castillo, N.; Aizpurua, M.; Roselló, E.; Bosch, F.; Valcárcel, D.
Abstract Invasive fungal infections (IFI) represent one of the most aggressive infectious complications among hematopoietic cell transplantation (HCT) recipients. Aspergillosis is the most frequent cause of IFI in allogeneic HCT (allo‐HCT), with most of the cases involving the respiratory tract. Other infrequent and usually more aggressive forms of invasive aspergillosis include hepatic, neurological, and gastrointestinal (GI). We report herein a case of GI aspergillosis diagnosed in a living patient, off all systemic immunosuppression after an allo‐HCT, who had undergone a permanent colostomy because of colon carcinoma 35 years before hematological diagnosis.